2015
DOI: 10.1590/1413-81232015203.16912013
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events and other incidents in neonatal intensive care units

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
21

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 39 publications
1
47
0
21
Order By: Relevance
“…A literature systematic review conducted between 2000 and 2011 in a population of newborns showed lower infection rates associated with the PIVC (16) . However, the infection rates can be triggered by several health care-related factors, considered preventable through the development of health educational practices with nursing professionals (17) . There was a higher risk of developing complications during catheter use (p = 0.0093) when related to the lower weight of neonates on the puncture day, because the inadequate development of their physiological aspects characterizes a risk factor for errors, including adverse events in newborns resulting in catheter loss (17) .…”
Section: Risk Factors Related To the Cathetermentioning
confidence: 99%
“…A literature systematic review conducted between 2000 and 2011 in a population of newborns showed lower infection rates associated with the PIVC (16) . However, the infection rates can be triggered by several health care-related factors, considered preventable through the development of health educational practices with nursing professionals (17) . There was a higher risk of developing complications during catheter use (p = 0.0093) when related to the lower weight of neonates on the puncture day, because the inadequate development of their physiological aspects characterizes a risk factor for errors, including adverse events in newborns resulting in catheter loss (17) .…”
Section: Risk Factors Related To the Cathetermentioning
confidence: 99%
“…In addition, it demonstrated that errors in the medication process are the major cause of adverse events in the NICU. When compared to the frequency of occurrence of the same errors in an adult ICU, the NICU has an incidence eight times higher (15) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to errors in the medication process, problems related to mechanical ventilation were observed, such as extubation failures and accidental extubation, most of which occur due to the absence of the cuff in endotracheal tubes for newborns (15) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Há uma elevada incidência de EAs nesta UTIN especialmente entre os RNs de muito baixo peso (4) . Outro estudo evidencia que os tipos de incidentes que mais ocorrem nas UTINs estão relacionadas a erros ou falhas no uso de medicamentos, infecção associada aos cuidados em saúde, lesão cutânea, ventilação mecânica e cateteres intravasculares (20) , fazendo assimilação com os achados desta pesquisa.…”
Section: Discussionunclassified